Principal-shared instructional leadership in differentiated instruction classrooms: its effect on pedagogical practices - Astutik, Pipit Pudji; Setyosari, Punaji; Santoso, Anang; Hadi, Syamsul; Kusumaningrum, Shirly Rizki (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This article examines the effect of principal-shared instructional leadership, learners’ characteristics, and differentiated instruction strategies support on the quality of pedagogical practices mediated by classroom interventions. This instructional strategy is used along with the implementation of the independent curriculum, and teachers have to pay attention deeply to students’ learning needs. This study was conducted as explanatory research on mover teachers throughout Indonesia, and 890 teachers participated voluntarily. Path analysis is utilized to estimate variables relationships. The study revealed that principal-shared instructional leadership and differentiated strategies positively and directly affect the quality of pedagogical practices, and learners’ characteristics only contribute to an indirect effect. The findings suggest that school principals have significant roles in mobilizing stakeholders and facilitating learning resources for providing classroom interventions appropriately for students to learn. As an implication, accomplishing the quality of pedagogical practices will be able to achieve students’ learning performances.